Almond breeding and evaluation activities in Central California: past and future - Ledbetter C.A. (XIV GREMPA Meeting on Pistachios and Almonds, 2010)
Almond breeding and evaluation efforts at the Agricultural Research Service resumed during the late 1980s after a lapse of nearly 20 years. Breeding efforts from the 1950s through the early 1970s led to a diverse collection of advanced selections, some being suitable as pollenizers for the important Nonpareil cultivar. Current evaluation efforts are now further characterizing the collection, and some selections are being used in a new breeding effort to develop self-compatible almonds. Through K-means analyses, we have identified those advanced selections from the former breeding effort that were most similar to Nonpareil in bloom phenology and nut/kernel characteristics. In long term storage trials, we have identified several advanced selections with reduced pellicle luminosity degradation rates as compared with Nonpareil. The Tuono cultivar has been our exclusive source of self-compatibility in the new breeding effort, with planned hybridizations emphasizing those advanced selections that are homozygous for sweet kernel. New self-compatible accessions are being identified in segregating seedling populations, and we currently evaluate 50-70 self-compatible accessions annually for nut/kernel quality. Recent evaluation efforts have demonstrated significant differences in shell cracking strength among almond varieties that are independent of an accession's kernel percentage, suggesting shell compositional or morphological differences. These differences may have implications in the use of specific shell types for granular activated carbons, or other value-added product applications.
14. GREMPA Meeting on Pistachios and Almonds, 2008/03/30-2008/04/04, Athens (Greece)